2014
DOI: 10.15288/jsad.2014.75.136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sensation Seeking on Response to Alcohol Versus Placebo: Implications for the Acquired Preparedness Model

Abstract: ABSTRACT. Objective: Previous research has identifi ed several aspects of behavioral undercontrol that are associated with heavy drinking and problems. Further, research on the acquired preparedness model (Smith and Anderson, 2001) has identifi ed biased learning as a potential mechanism of these effects. Traits like sensation seeking have been linked to stronger positive and weaker negative expectancies, which, in turn, contribute to increased risk for heavy drinking and problems. Although expectancies are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
(60 reference statements)
5
18
1
Order By: Relevance
“…Findings also showed that ADHD symptoms predicted steeper increases in stimulation, but only on the ascending limb. In contrast to prior studies of sensation seeking and related personality traits (e.g., Erblich & Earleywine, 2003; Fillmore, et al, 2009; Leeman, et al, 2014; Scott & Corbin, 2014), sensation seeking did not moderate changes in subjective stimulation. Because the association of subjective stimulant or sedative effects with motivational indicators (e.g., craving, wanting) may have etiological relevance (King, et al, 2011), further laboratory studies of these associations, including the examination of individual or pharmacological (e.g., BAC limb) moderators, is likely important.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings also showed that ADHD symptoms predicted steeper increases in stimulation, but only on the ascending limb. In contrast to prior studies of sensation seeking and related personality traits (e.g., Erblich & Earleywine, 2003; Fillmore, et al, 2009; Leeman, et al, 2014; Scott & Corbin, 2014), sensation seeking did not moderate changes in subjective stimulation. Because the association of subjective stimulant or sedative effects with motivational indicators (e.g., craving, wanting) may have etiological relevance (King, et al, 2011), further laboratory studies of these associations, including the examination of individual or pharmacological (e.g., BAC limb) moderators, is likely important.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding extends prior work (Brunelle et al, 2004; Erblich & Earleywine, 2003; Leeman et al, 2014; Scott & Corbin, 2014) and provides initial evidence for one mechanism by which personality influences drinking habits. However, important next steps are to determine whether the association of reward sensitivity and acute stimulation is best accounted for by the pharmacological and/or expectancy effects of alcohol, and, further, whether findings extend to more diverse samples and age groups and at varied doses of alcohol.…”
Section: Discussionsupporting
confidence: 85%
“…Of the various ways that personality promotes alcohol misuse (Littlefield & Sher, 2010), one that has gained increasing research attention is the contribution of personality to subjective response to alcohol (Erblich & Earleywine, 2003; Leeman et al, 2014; Scott & Corbin, 2014). Subjective response is implicated in virtually all theoretical models of alcohol misuse (Newlin & Renton, 2010; Schuckit, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the present study focused on drinking motives as predictors of subjective responses to alcohol in order to test specific hypotheses informed by motivational theory that have not yet been fully examined. However, there are other individual difference factors that are known to influence subjective responses to alcohol, including alcohol expectancies, personality traits, and family history of alcoholism (Morean et al., ; Quinn and Fromme, ; Scott and Corbin, ). Future studies using larger samples will permit more comprehensive analyses of individual differences in subjective responses to alcohol.…”
Section: Discussionmentioning
confidence: 99%